Developmental language disorders in Cyprus: mapping speech and language service provision to vulnerable children. - Theodorou, Elena; Kambanaros, Maria; Petinou, Kakia (Journal of Monolingual & Bilingual Speech (JMBS), 2022)
The term developmental language disorder (DLD) refers to the condition in which a child fails to achieve the speech and language milestones that are expected for his/her chronological age. The disorder is often linked to a series of add-on effects such as learning difficulties, trouble with socializing, problematic behaviour and low self-esteem. According to the international literature, DLD affects approximately 7% of school children in mainstream education. This paper reports on research conducted in Cyprus aiming to map the services provided by speech and language therapists (SLTs) to children with DLD. A questionnaire containing key areas of enquiry was developed and distributed to professionals working with DLD in Cyprus. A total of 44 responses were submitted by SLTs who provide services to individuals with DLD. The findings showed that the majority of children with DLD are diagnosed with a mixed receptive/expressive language disorder and are, on average, 7 years of age. The speech therapy interventions provided by professionals were twice a week and were most often on an individual basis. The maximum number of sessions was not pre-determined. Findings underscored the need for further research in defining service provision issues for children with DLD in Cyprus.